2014
DOI: 10.1088/0953-2048/28/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

High transportJcin magnetic fields up to 28 T of stainless steel/Ag double sheathed Ba122 tapes fabricated by scalable rolling process

Abstract: Abstract:The recently discovered iron-based superconductors with very high upper critical field (H c2 ) and small anisotropy have been regarded as a potential candidate material for high field applications. However, enhancements of superconducting properties are still needed to boost the successful use of iron-based superconductors in such applications. Here, we propose a new sheath architecture of stainless steel (SS)/Ag double sheath and investigate its influence on the microstructures and J c -H property.We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 43 publications
4
70
1
Order By: Relevance
“…Based on the collective pinning model [42], the condition that the above formulas are applicable is H < BSB ~ 5(Jc/Jd)Hc2, where Jd is the depairing current. In the case of K-Ba122 (x = 0.30), BSB is estimated as ~1.5 T using Jc ~ 6 × 10 5 The blue-dashed and the red-dashed curves are the contributions from the Tc pinning and the l pinning, and the black-dashed curves are their sums, respectively. For x = 0.23, the l pinning is larger than the Tc pinning at low T. With increasing T, the Tc pinning increases, and becomes dominant at T > 10 K.…”
Section: Temperature Dependence Of Jcmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the collective pinning model [42], the condition that the above formulas are applicable is H < BSB ~ 5(Jc/Jd)Hc2, where Jd is the depairing current. In the case of K-Ba122 (x = 0.30), BSB is estimated as ~1.5 T using Jc ~ 6 × 10 5 The blue-dashed and the red-dashed curves are the contributions from the Tc pinning and the l pinning, and the black-dashed curves are their sums, respectively. For x = 0.23, the l pinning is larger than the Tc pinning at low T. With increasing T, the Tc pinning increases, and becomes dominant at T > 10 K.…”
Section: Temperature Dependence Of Jcmentioning
confidence: 99%
“…To evaluate their current carrying ability, various experiments have been carried out so far. In most cases, encouraging results have been obtained, such as a high Jc exceeding 10 5 A/cm 2 even under high-Hs above 10 T [4,5], a moderate anisotropy of Jc in superconducting tapes with respect to the direction of the applied H [6,7], superior inter-grain connectivity [8], etc. It was also demonstrated that the introduction of artificial pinning centers by irradiation with heavy-irons, neutrons, electrons, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Mainly, two pressing methods for the fabrication of IBS wires and tapes have been proven to be effective in enhancing J c , namely, uniaxial pressing for the tape [32][33][34][35][36] and hot isostatic pressing (HIP) for round wires [21,23,39,40]. Although uniaxial-press method has realized the highest J c value, it cannot be used for the fabrication of round wires.…”
mentioning
confidence: 99%
“…Previously, monofilamentary PIT Sr(Ba)-122/Ag composites conductors with iron [19,20], copper [21,22] and stainless steel [23] conductors with large filament number and very fine filaments are needed in order to reduce the AC loss induced by the eddy currents in metallic matrix and the interfilamentary coupling currents [18]. Therefore, in this work, 7-, 19-and 114-filament Sr-122/Ag/Fe composite conductors were prepared.…”
mentioning
confidence: 99%